UPAYA MENINGKATKAN MOTIVASI BELAJAR MATEMATIKA MELALUI GAME MATEMATIKA ONLINE PADA SISWA SMP - Andriani Andriani; Rika Silviani; Lia Rista; Cut Yuniza Eviyanti (STKIP Andi Matappa, 2021)
The weak motivation to learn mathematics in junior high school students is caused by many factors including lack of teacher effort in using media to help students understand and grow motivation in learning mathematics. This research aims to determine the difference to improve in motivation to learn mathematics through online mathematics games higher than conventional learning. This study uses a quantitative approach. The population in this study were all class students VIII SMPN Negeri 2 Lhokseumawe, SMP Negeri 3 Lhokseumawe and SMP Swasta Sukma Bangsa Lhokseumawe. Sample selection using random sampling technique class. Collecting data using motivation questionnaires and observation sheets. Analysis of the results showed that there was improve in the motivation of students taught using online mathematics games higher than students who were taught conventionally in SMP in Lhokseumawe City.